Association of rno‐miR‐183‐96‐182 cluster with diethyinitrosamine induced liver fibrosis in Wistar rats. Issue 5 (25th January 2018) - Chandel, Rajeev; Saxena, Roli; Das, Ashim; Kaur, Jyotdeep
ABSTRACT: Chronic liver injury due to various etiological factors including environmental carcinogens results in development of liver fibrosis. Numerous studies showed role of miRNAs in liver fibrosis. In the present study, we determined the rno‐miR‐183‐96‐182 cluster expression during hepatic fibrosis induced by diethylnitrosamine (DEN) treated Wistar rats and its association with plasma levels of circulating rno‐miR‐96, rno‐miR‐182, rno‐miR‐183, liver function test and lipid profile, aiming to identify their potential for histological stratification and early diagnosis of liver fibrosis. We found significant upregulation in the hepatic expression of rno‐miR‐183‐96‐182 cluster upon development of fibrosis in a DEN treated rats. Interestingly, the hepatic expression of this miRNA cluster correlates positively with the progression of fibrosis. Univariate analysis showed that hepatic expression of rno‐miR‐182‐5p and rno‐miR‐183‐5p and plasma activity of ALT are significant predictors of fibrosis. Multivariate logistic regression analysis revealed a panel of rno‐miR‐182‐5p and ALT that can discriminate F2‐F3 from F0‐F1 (AUC = 0.87; P ‐value < 0.001), F4‐F5‐F6 from F0 to F1 (AUC = 0.981; P ‐value < 0.001), and F4‐F5‐F6 from F2 to F3 (AUC = 0.824; P ‐value < 0.001). A significant positive correlation of rno‐miR‐183‐96‐182 cluster members was also observed with plasma activities of ALT, AST, ALP, and levels of total cholesterol, HDLc and LDLc during fibrosis progression in DEN treated Wistar rats. Thus, it can be concluded that rno‐miR‐183‐96‐182 cluster being significantly up regulated and associated with chronic liver disease might play a role in fibrosis maintenance and progression. A panel of rno‐miR‐182‐5p and ALT being significant predictors of fibrosis might improve histological stratification of fibrosis staging. Abstract : The present study showed that rno‐miR‐183‐96‐182 cluster being significantly up regulated and associated with liver fibrogenesis might play a role in fibrosis development and progression and could be useful for improved histological stratification of fibrosis staging whereas its knockdown can be used therapeutically.